Spatiotemporal variations of eco-environmental vulnerability in Shiyang River Basin, China - Xu, Cundong; Hu, Xiaomeng; Wang, Xin; Liu, Zijin; Tian, Junjiao; Ren, Zihao (Ecological indicators, 2024)
•Coupling CM-AHP and EWM to evaluate the eco-environmental vulnerability.•The spatiotemporal changes of eco-environmental vulnerability are shown on GIS.•The overall evolution of eco-environmental vulnerability has been positive.•Providing a valid reference for sustainable development of the Shiyang River Basin. Eco-environmental vulnerability reflects the unfavorable degree of the ecological environment presented by external disruptions. The Shiyang River Basin, as a typical desert interior river basin in Northwest China, plays crucial ecological roles. Exploring eco-environmental vulnerability's spatial and temporal evolution is vital to maintaining ecosystem stability. We utilized the ecological sensitivity-resilience-press (SRP) model to create a complete evaluation index system of eco-environmental vulnerability using meteorological, remote sensing, and statistical data. The cloud theory improved analytic hierarchy process (CM-AHP) was used to calculate the subjective weights, the entropy weight method (EWM) was used to estimate the objective weights, and the comprehensive weights of the indicators were determined using the least square method, which combined the subjective and objective weights. From 2000 to 2020, the spatial-temporal features of eco-environmental vulnerability in the research area were analyzed. The results indicate that surface temperature, land use, and monthly precipitation are key factors impacting the state of eco-environmental vulnerability. The basin's potential-vulnerable and light-vulnerable areas are predominantly located in the south and southwest, whereas the northern and eastern areas are classified as severe-vulnerable and extreme-vulnerable. Extreme-vulnerable areas declined from 8.59% in 2000 to 4.3% in 2020, while potential-vulnerable areas climbed from 2.11% in 2000 to 8.08% in 2020. The eco-environmental vulnerability as a whole has evolved in a benign direction. The research results can serve as a theoretical groundwork for the restoration of the Shiyang River Basin's ecological environment and long-term development.